Environment-based approach to the management of an institution of inclusive education - Сhernenko Nataliia; Sakalіuk Oksana (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2020)
The article focuses on the problems related to the management of an educational institution applying the environment-based approach under conditions of an inclusive education model. The purpose of the article is to characterise the environment-based approach as a basis for the implementation of inclusive education in establishments of general secondary education. To achieve the goals and objectives of the study, these theoretical and empirical methods were used (analysis, synthesis, generalisation and systematisation of the basic provisions for the implementation of the environment-based approach into the practice of management of educational institutions specialised in inclusive education; questionnaire method). It is emphasised that the application of the environment-based approach to the management of an institution of inclusive education involves the formation and development of an inclusive learning environment taking into account its structural components: spatial-objective, content-centred and methodological, communicative-organisational. Some problems in the practical implementation of the environment-based approach have been revealed: education managers encounter the primary problems that are related to the implementation of inclusive education into establishments of general secondary education; they concern the issues regarding the development and improvement of the main structural components of an inclusive learning environment. The importance of a step-by-step implementation of the environment-based approach to the management of an institution of inclusive education (the diagnosis and modelling of the environment, the production of educational results), which will help create an inclusive learning environment in which children with special educational needs will feel most comfortable. It is concluded that the environment-based approach represents the strategy of indirect management in education and considers the environment as a key means of solving management-related problems of transferring an educational institution into the mode of inclusive education functioning and developing teachers’ readiness to master and implement inclusive education.